CCR2-deficient mice are protected to sepsis by the disruption of the inflammatory monocytes emigration from the bone marrow. Issue 6 (5th October 2020) - Cebinelli, Guilherme Cesar Martelossi; de Lima, Kalil Alves; Silva Castanheira, Fernanda Vargas e; Hiroki, Carlos Hiroji; Monteiro, Valter Vinícius Silva; de Lima, Mikhael Haruo Fernandes; Nascimento, Daniele Carvalho Bernardo; Alves Filho, José Carlos; Cunha, Thiago Mattar; Cunha, Fernando de Queiroz
Abstract: Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. Inflammatory monocytes are recruited to both the infection site and vital organs during sepsis; however, the mechanisms that orchestrate their migration, as well as the participation of these cells in systemic inflammation and vital organ damage, are still not fully elucidated. In this context, we described that CCR2-deficient mice had diminished migration of inflammatory monocytes from bone marrow to the circulation and subsequently to the site of infection and vital organs during cecal ligation and puncture (CLP)-induced polymicrobial sepsis. The reduction in the migration of inflammatory monocytes to the infection site was accompanied by a significant increase in the number of neutrophils in the same compartment, which seemed to counterbalance the absence of inflammatory monocytes in controlling microbial growth. Indeed, wild-type (WT) and CCR2-deficient mice under CLP presented similar control of infection. However, the CCR2-deficient mice were more resistant to sepsis, which was associated with a decrease in inflammatory mediators and organ damage biomarkers. Furthermore, the systemic adoptive transfer of CCR2-WT or CCR2-deficient inflammatory monocytes into CCR2-deficient mice equally increased the susceptibility to sepsis, demonstrating the deleterious role of these cells in the periphery even when CCR2 is absent. Thus, despite the host-protective role of inflammatory monocytes in controlling infection, our results demonstrated that the mechanism by which CCR2 deficiency shows protection to CLP-induced sepsis is due to a decrease of inflammatory monocytes emigration from bone marrow to the circulation and vital organs, resulting in the reduction of organ damage and systemic cytokine production. Graphical Abstract: CCR2-deficiency shows protection to CLP-induced sepsis due to a decrease of inflammatory monocytes emigration from bone marrow to the circulation and vital organs, resulting in the reduction of organ damage and systemic cytokine production.